Swift recipes for iOS developers : real-life code from App Store apps - Nekrasov, Alexander (Apress, 2022)
Boost your iOS developer career by learning from real-life examples and start writing code for one of the most successful platforms ever. No matter if you're an experienced developer or just a beginner, you'll find something new and something useful for your future projects here. All of the recipes in this book are taken from real-life commercial projects that have been approved by Apple and published on the App Store. You won't write "Hello, world!" and similar programs. Instead you'll see how to parse different data formats; run JavaScript code right inside your iOS app; and enhance storyboard editor with several simple extensions. You'll make beautiful modern-looking dialogs with blurs, shadows and rounded corners using only a few lines of code, and safely convert data after analyzing text strings. Go on to animate your layout and get your app shored up to crash as little as possible Each recipe offers a code snippet to copy and paste to your project as a tool to boost your knowledge, as well as, create plug-and-play features. Each of recipe shows the description for each line of code while explaining the logic of it, contains references to documentation, and gives you an opportunity to modify or write something similar that fits your project better. A good piece of code should not work but also be short, clear, and stable. And that combo will be our priority in these code recipes. Well-written code snippets must run in any environment and be easily transferrable from one project to another. Most of the provided recipes will migrate from one project to another with little to no changes at all, and with years of real-world application have proven themselves to be useful and stable. Dive into the world of iOS development and write clear, functioning, and safe Swift code! What You'll Learn Parse, convert, and print Swift data Develop stunning UIs quickly Write effective and portable Swift extensions Make your code cleaner and safer Who This Book Is For Beginners in iOS development who want to improve their skills with real-life examples. Developers switching to mobile development from other areas. All iOS developers looking for code recipes.